First you'd need to multiply 99 by 22.
14 ( 6x - 3 ) = 99 × 22
14 ( 6x - 3 ) = 2,178
Next, you'd divide both sides by 14.
14 ( 6x - 3 ) = 2,178
![\displaystyle(14(6x-3))/(14) = (2,178)/(14)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/25uaavd0z8qbrc0xih5wcf5co9bpxnqna5.png)
![\displaystyle\ 6x - 3 = (2,178)/(14)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/as6com6xtmvq887qzdiatfcpy4y1tyfl44.png)
Now simplify 2,178 over 14.
![\displaystyle\ 6x - 3 = (2,178)/(14)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/as6com6xtmvq887qzdiatfcpy4y1tyfl44.png)
![\displaystyle\ 6x - 3 = (1,089)/(7)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/yt15l4rzeamhv0fatj4c8dbrigxeb2g62t.png)
Now add 3 to both sides to get rid of -3.
![\displaystyle\ 6x - 3 = (1,089)/(7)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/yt15l4rzeamhv0fatj4c8dbrigxeb2g62t.png)
![\displaystyle\ 6x - 3 + 3= (1,089)/(7) + 3](https://img.qammunity.org/2019/formulas/mathematics/middle-school/30ey93srxihnk6jionu9u5axsef5cyxfoo.png)
![\displaystyle\ 6x = (1,110)/(7)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/25ga5vidnzakei9kqymy7uvdig5njhd0su.png)
Now divide both sides by 6 to get x alone.
![\displaystyle\ 6x = (1,110)/(7)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/25ga5vidnzakei9kqymy7uvdig5njhd0su.png)
![\displaystyle(6x)/(6) = ((1,110)/(7))/(6)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/26vv39x39k5r7sxa4kxliuegv4om069s7l.png)
![\displaystyle\ x = (185)/(7)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/nd0o05ud1k5tubkcqt3xxfno7jmpbb7iqy.png)
Now we simplify.
![\displaystyle\ x = (185)/(7)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/nd0o05ud1k5tubkcqt3xxfno7jmpbb7iqy.png)
![\displaystyle\ x = 26(3)/(7)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/q0i7biece76ezq18dl98cx1abwp8h9xvsm.png)
|
|
- Marlon Nunez